2020
DOI: 10.1186/s12891-020-3106-y
|View full text |Cite
|
Sign up to set email alerts
|

The value of dynamic MRI in the treatment of cervical spondylotic myelopathy: a protocol for a prospective randomized clinical trial

Abstract: Background Cervical spondylotic myelopathy (CSM) is the most severe type of cervical spondylosis and the most common cause of spinal cord dysfunction among adults over 55 years old. MRI plays an important role in the diagnosis and evaluation of CSM, which can directly demonstrate the correlation between disc, spinal cord, posterior structures and abnormal signal in spinal cord. Static MRI can only show the static and neutral position of spinal cord, which is not enough to understand the pathogenesis of CSM. Dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Elderly age was shown to predict increased stenosis in extension. With utilization of dynamic scans, clinician agreement and consensus in interpretation improved [ 1 , 3 , 5 , 11 ]. In the present study, we showed that the number of compression levels was increased by 17 levels in extension MR images in 12 or 50% of our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly age was shown to predict increased stenosis in extension. With utilization of dynamic scans, clinician agreement and consensus in interpretation improved [ 1 , 3 , 5 , 11 ]. In the present study, we showed that the number of compression levels was increased by 17 levels in extension MR images in 12 or 50% of our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Los estudios electrofisiológicos no se usan de manera habitual para diagnosticar la mielopatía cervical, pero pueden ser útiles para descartar otras afecciones, como el síndrome del túnel carpiano, la esclerosis múltiple, la esclerosis lateral amiotrófica, la degeneración combinada subaguda y otras enfermedades neurológicas que muestran patrones electromiográficos característicos 25 .…”
Section: Evaluación Radiográficaunclassified
“…38 Although comprehensive comparative studies are still outstanding, retrospective studies have shown extension-MRI views to more consistently identify canal stenosis that was absent on flexion or neutral MRIs up to 22.5% of the time 39,40. Randomized controlled trials aimed at studying the value of dynamic MRI in the diagnostics of DCM are currently underway 41…”
Section: Current Imaging Modalitiesmentioning
confidence: 99%
“…39,40 Randomized controlled trials aimed at studying the value of dynamic MRI in the diagnostics of DCM are currently underway. 41…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%